A way through the maze: Exploring differences and overlaps between wellness and medical tourism providers - Voigt, Cornelia; Laing, J. (2013)
The aims of this chapter are as follows: •to develop a typology of medical and wellness tourism providers and to explore differences and overlaps between the two forms of tourism; •to examine five provider models where the lines between medical and wellness tourism have been blurred; •to compare the concept of wellness with the biomedical conception of health; •to provide background information on the broader environment of health care and Western consumer culture, both of which have influenced or played a role in the development of these provider models; •to discuss areas for future research.